Social support as a moderator of positive psychological strengths and subjective well-being - Khan, A.; Husain, A. (2010)
The present study was conducted to examine: (a) the relation of positive psychological strengths, i.e., hope, optimism, self-efficacy, and resiliency, with subjective well-being, and (b) the role of social support as a moderator of positive psychological strengths and subjective well-being. The following hypotheses were proposed: (a) that positive psychological strengths would be positively related with subjective well-being and social support; (b) social support would moderate the relation of positive psychological strengths with subjective well-being. 116 men and 64 women (M age = 21.53 yr., SD = 4.99, range = 33) from India participated. Significant positive relationships were found for positive psychological strengths with subjective well-being and with social support network (family, friends, and others). Regression analysis showed social support significantly moderated the relations of positive psychological strengths with subjective well-being.